Study of Venography technique in digits of cows - Loureiro, M. G. (2019)
The aim of this study was to describe the technique of retrograde venography foot in cows, comparing the approaches of the dorsal common digital vein III with the digital commons II or IV, thoracic and pelvic by administering two different volumes of contrast members. Fifty three fore and hindlimbs of 14 cows were used, a rubber tourniquet was placed at 5cm above accessory digit. Diatrizoatemeglumine was administered at 10mL to 24 members (group 1), 13 dorsal common digital vein III for access 1 (A1), and 11 digital II or IV access 2 (A2). In group 2 20mL was administered to 29 members, 15 by 19 in A1 and A2. After contrast administration, the radiographs were repeated every 20 seconds until 120 seconds. The degree of vascular filling was greater in group 2, independent of venous access, member or moment. There was no significant difference in the degree of radiopacity of radiographic images when compared to the venous access, time and a member of both groups. We conclude that administration of 20mL of contrast showed better vascular filling and radiopacity, with no difference between 20 and 120 seconds after contrast administration in independent radiographic quality venous access.